2015
DOI: 10.1177/1354068815593453
|View full text |Cite
|
Sign up to set email alerts
|

How campaigns polarize the electorate

Abstract: The minimal effect theory of campaign studies stipulates that intense political competition during campaigns assures and reinforces the initial party choice of the electorate. We find that this reinforcement is two-fold. During the campaign, the party preference of the voters’ in-group party increases while the party preference of the voters’ out-group parties decreases. Voters’ preference for their most preferred party (MPP) increases during the election campaign, while their preference for their least liked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 26 publications
1
17
0
1
Order By: Relevance
“…These mixed findings about reactions to the COVID-19 pandemic can thus be steered by elite cues. Prior research has shown that elite cues and polarized political debate can have a decisive impact on political attitude formation and voting behavior in normal times (Zaller, 1992;Mondak, 1993;Lupia, 1994;Druckman et al, 2013) or during electoral campaigns (Hansen and Kosiara-Pedersen, 2017) and intense or biased media coverage (Levendusky, 2013;Levendusky and Malhotra, 2016). However, there is little evidence about the influence of elite cues during a pandemic in which individual behavior affects not only political outcomes but also personal health (Grossman et al, 2020).…”
Section: Polarization During the Covid-19 Pandemicmentioning
confidence: 99%
“…These mixed findings about reactions to the COVID-19 pandemic can thus be steered by elite cues. Prior research has shown that elite cues and polarized political debate can have a decisive impact on political attitude formation and voting behavior in normal times (Zaller, 1992;Mondak, 1993;Lupia, 1994;Druckman et al, 2013) or during electoral campaigns (Hansen and Kosiara-Pedersen, 2017) and intense or biased media coverage (Levendusky, 2013;Levendusky and Malhotra, 2016). However, there is little evidence about the influence of elite cues during a pandemic in which individual behavior affects not only political outcomes but also personal health (Grossman et al, 2020).…”
Section: Polarization During the Covid-19 Pandemicmentioning
confidence: 99%
“…Hetherington, 2001;Abramowitz and Saunders, 2008;Adams et al, 2012b;Lupu, 2015). This matters because polarization and its potential negative effects, such as higher dissatisfaction with democracy among supporters of the losing side (Iyengar et al, 2012) or worse government performance (Sørensen, 2014), are not restricted to two-party systems (Hansen and Kosiara-Pedersen, 2015). Elite polarization may lead consensual and consociational democracies into a centrifugal path, often associated with unstable regimes, as Vatter (2016) argues is happening in Switzerland.…”
Section: Introductionmentioning
confidence: 99%
“…The second and third hypotheses follow obviously from the discussion above, but it might not be apparent why the first one, stipulating that interest in EU increases as the campaign commences, follows from the literature on campaign effects. However, we believe that interest is a measure, albeit imperfect, of the increased engagement with politics which have been identified as a result of campaigns (Hansen and Pedersen 2014, 305). As such, extant literature has found that being subject to more political information almost inadvertently makes voters more politically engaged (Jung, Kim and de Zúñiga 2011).…”
Section: Campaign Effects and Electoral Democracy In The Eumentioning
confidence: 99%
“…There are three main ways in which increased information can influence voters: (1) it informs voters of candidate positions (Hansen and Pedersen 2014), (2) it provides voters with opportunities to find their own position (Lenz 2009) and (3) it can prime voter interest on the issues that the information centers on (Krosnick and Kinder 1990). In the context of European Parliament elections, we would expect campaigns, and the information flow that comes with it, will affect voters in a similar manner, which, we argue, will result in issue voting on EU issues.…”
Section: Campaign Effects and Electoral Democracy In The Eumentioning
confidence: 99%
See 1 more Smart Citation